{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

30-calculating-definite-integrals

# 30-calculating-definite-integrals - Math 1a Calculating...

This preview shows pages 1–4. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 1a Calculating Definite Integrals Fall, 2009 ’ & \$ % The Definite Integral If F ( x ) is any anti-derivative of f ( x ) (that is, if F ( x ) = f ( x )), then the definite integral of f ( x ) from a to b is Z b a f ( x ) dx = F ( x ) b a = F ( b )- F ( a ) . Compute the following definite integrals: 1 Z 6 1 (4 x + 2) dx 2 Z 9 1 √ x dx 3 Z 1 ( x- x 2 ) dx 4 Z 3 ( x 2- 4 x ) dx 5 Z e 1 1 x dx 6 Z 5- 5 ( x 3 + x ) dx 7 Z 1 2 x dx 8 Z 1 e x dx 9 Z 1 a x dx , a > 10 Z π/ 4 sec( x ) tan( x ) dx 11 Z 1 1 1 + x 2 dx 12 Z 1 / 2 1 √ 1- x 2 dx 13 Z π/ 4 1 + cos 2 ( x ) cos 2 ( x ) dx 14 Z- 3 e x +3 dx 15 Z 2 1 x 2 + 2 x- 3 x dx 16 (a) Verify that d dx ( x ln( x )- x ) = ln( x ). (b) Use part (a) to compute Z e 1 ln( x ) dx . 17 What is wrong with the following computation of the area under y = 1 /x 4 from x =- 1 to x = 1? Area = Z 1- 1 x- 4 dx = x- 3- 3 1- 1 = 1- 3-- 1- 3 =- 2 3 . (Notice that the function is always positive, yet the area underneath the curve is negative! So there must be something wrong.) 18 Find the area of the region bounded by the give curve and the x-axis over the given interval: (a) y = cos( x ),- π 2 ≤ x ≤ π 2 (b) y = x 3- 4, ≤ x ≤ 2 Calculating Definite Integrals – Answers / Solutions 1 Z 6 1 (4 x + 2) dx = ( 2 x 2 + 2 x ) 6 1 = ( 2(6) 2 + 2(6) )- ( 2(1) 2 + 2(1) ) = 80 2 Z 9 1 √ x dx = x 3 / 2 3 / 2 9 1 = 2 3 ( 9 3 / 2- 1 3 / 2 ) = 52 3 ≈ 17 . 3333 3 Z 1 ( x- x 2 ) dx = 1 2 x 2- 1 3 x 3 1 = 1 6 4 Z 3 ( x 2- 4 x ) dx = 1 3 x 3- 2 x 2 3 = 1 3 3 3- 2(3) 2- 1 3 3- 2(0) 2 =- 9 5 Z e 1 1 x dx = ln( x ) e 1 = ln( e )- ln(1) = 1 6 Z 5- 5 ( x 3 + x ) dx = 1 4 x 4 + 1 2 x 2 5- 5 = 1 4 (5) 4 + 1 2 (5) 2- 1 4 (- 5) 4 + 1 2 (- 5) 2 = 0 7 Z 1 2 x dx = 2 x 1 ln(2) 1 = 2 1- 2 ln(2) = 1 ln(2) 8 Z 1 e x dx = e x 1 = e 1- e = e- 1 9 Z 1 a x dx = a x 1 ln( a ) 1 = a 1- a ln( a ) = a- 1 ln( a ) unless a = 1, in which case this is the integral of y = 1 from...
View Full Document

{[ snackBarMessage ]}

### Page1 / 5

30-calculating-definite-integrals - Math 1a Calculating...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online